2023
DOI: 10.20473/jn.v18i1.42404
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of illness representations in patients with mild traumatic brain injury

Abstract: Introduction: Little is known about the cognitive and emotional perceptions of patients with mild traumatic brain injury, although studies showed patients experiencing difficulties in cognitive functioning and psychological impacts following their injury. This systematic review aims to identify the current literature regarding illness representation dimensions in mild traumatic brain injury and their related factors. Methods: A search of electronic databases was completed using PubMed, CINAHL, Embase, and Web … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Specifically, in mTBI, a previous study reported a relationship between illness perceptions (IP) and QOL (War and Rajeswaren, 2013). Furthermore, a systematic review of mTBI patients reported that some dimensions of illness perception were found to have relationships to post-traumatic stress disorder and the quality of life of mild traumatic brain injury patients (Mulyadi, Tonapa, et al, 2023). The phrases "illness perceptions" and "illness representations," which refer to people's perspectives when they come across health risks, are frequently used synonymously (Diefenbach and Leventhal, 1996;Tonapa et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in mTBI, a previous study reported a relationship between illness perceptions (IP) and QOL (War and Rajeswaren, 2013). Furthermore, a systematic review of mTBI patients reported that some dimensions of illness perception were found to have relationships to post-traumatic stress disorder and the quality of life of mild traumatic brain injury patients (Mulyadi, Tonapa, et al, 2023). The phrases "illness perceptions" and "illness representations," which refer to people's perspectives when they come across health risks, are frequently used synonymously (Diefenbach and Leventhal, 1996;Tonapa et al, 2023).…”
Section: Introductionmentioning
confidence: 99%